Medium‐chain dehydrogenase/reductase and aldo‐keto reductase scavenge reactive carbonyls in Synechocystis sp. PCC 6803. Issue 6 (23rd February 2018) - Shimakawa, Ginga; Kohara, Ayaka; Miyake, Chikahiro
Abstract : Reactive carbonyls (RCs), which are inevitably produced during respiratory and photosynthetic metabolism, have the potential to cause oxidative damage to photosynthetic organisms. Previously, we proposed a scavenging model for RCs in the cyanobacterium Synechocystis sp. PCC 6803 (S. 6803). In the current study, we constructed mutants deficient in the enzymes medium‐chain dehydrogenase/reductase (ΔMDR) and aldo‐keto reductase (ΔAKR) to investigate their contributions to RC scavenging in vivo . We found that treatment with the lipid‐derived RC acrolein causes growth inhibition and promotes greater protein carbonylation in ΔMDR, compared with the wild‐type and ΔAKR. In both ΔMDR and ΔAKR, photosynthesis is severely inhibited in the presence of acrolein. These results suggest that these enzymes function as part of the scavenging systems for RCs in S. 6803 in vivo . Abstract :